Tales from a not-so-smart Miss Know-It-All - Russell, Rachel Renee (New York : Aladdin, 2012)
Nikki Maxwell, having joined the school newspaper staff in an effort to keep details about her crush on Brandon out of Mackenzie's gossip column, is assigned to be the advice columnist, but after getting flooded with letters asking for her guidance, she becomes overwhelmed and must ask her friends Chloe and Zoey for help.
5.0
3-6
750
Keywords: Advice columns -- Juvenile fiction; Newspapers -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Advice columns -- Fiction; Newspapers -- Fiction; Middle schools -- Fiction; Diaries -- Fiction; Schools -- Fiction; Diary fiction; School stories